Status of Health and Welfare Schemes of Women in Tamil Nadu - .E, Sathishkumar; S. , Parthiban; Kumar, Aswini (International Journal of Psychosocial Rehabilitation, 2020)
The Health and welfare of women constitute the most substantial contributing factor to human prosperity. According to the 2011 census of the Government of India, 67.7 percent of the total populations are women and children. India has committed to achieving the target of 2015 - United Nations Sustainable Development Goal (SDG) by 2030. Ever since, particularly in the health and welfare sector, the government has been taking various measures to attain the goal. In the case of Tamil Nadu, the government initiates and implements several social welfare schemes, programs, and protective legislative policies, mainly exclusive focus on the development of women and children in various aspects. As well, the State government introduced socioeconomic development schemes for the empowerment of women and endeavors to improve their socio-economic status. This research study will examine the condition of SDG Health Index of Tamil Nadu and its achievements in recent years. The study mainly focuses on the status of women's health and welfare in Tamil Nadu and analyzes the welfare and protection schemes for the wellbeing of women.